2014
DOI: 10.1371/journal.pone.0100825
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Static Magnetic Field Stimulates Quorum Sensing Circuit in Luminescent Vibrio Strains of the Harveyi Clade

Abstract: In this study, the evidence of electron-dense magnetic inclusions with polyhedral shape in the cytoplasm of Harveyi clade Vibrio strain PS1, a bioluminescent bacterium living in symbiosis with marine organisms, led us to investigate the behavior of this bacterium under exposure to static magnetic fields ranging between 20 and 2000 Gauss. When compared to sham-exposed, the light emission of magnetic field-exposed bacteria growing on solid medium at 18°C ±0.1°C was increased up to two-fold as a function of dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…In the present investigation, QS is only related to the colony formation, but more generally it may be responsible for other collective physical signals, as bioluminescence. As a matter of facts, although qualitatively, bioluminescent signals [26] have certain similarities to the QS signal that we observe in our simulations during biofilm formation. The analysis of the statistical properties of the observed QS signal will be carried out in future developments, in agreement with previous studies [23,24].…”
Section: Discussionsupporting
confidence: 70%
“…In the present investigation, QS is only related to the colony formation, but more generally it may be responsible for other collective physical signals, as bioluminescence. As a matter of facts, although qualitatively, bioluminescent signals [26] have certain similarities to the QS signal that we observe in our simulations during biofilm formation. The analysis of the statistical properties of the observed QS signal will be carried out in future developments, in agreement with previous studies [23,24].…”
Section: Discussionsupporting
confidence: 70%
“…The effect of magnetic field is still controversial in literature data. Potenza, et al 17 (2004) stated that the magnetic field improves the E. coli proliferation, although Talà, et al 21 (2014) noted no differences in proliferation for a V. harveyi related strain.…”
Section: Discussionmentioning
confidence: 99%
“…There are controversial opinions about microbe growth. For example, the results of experiments with the well-studied Vibrio campbellii strain BB120 (originally classified as Vibrio harveyi ) and derivative mutants unable to synthesize autoinducers suggest that the effects of magnetic fields on quorum sensing may be mediated by AI-2, the interspecies quorum sensing signal molecule 21 . Kohno, et al 15 (2000) has stated that growth under static magnetic field depends on the experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Their members are commonly used as models to study bacterial luminescence [35,36], QS [37], biofilm formation [38] and multi-chromosomal genome organization [39,40]. These bacteria play important roles in marine ecosystems because they establish mutualistic, commensalistic or parasitic symbiosis with a wide range of marine invertebrates and vertebrates [18,[41][42][43][44][45][46]. In particular, V. jasicida has been isolated from packhorse lobster, abalone, Atlantic salmon [29], Polychaeta [46], and some Hydrozoa and Bryozoa species [28].…”
Section: Experimental Set-up 21 Vibrio Jasicidamentioning
confidence: 99%
“…However, it is now clear [5,[8][9][10][11][12][13][14][15][16] that AI concentration could be affected by several environmental factors other than cell density, such as AI diffusion, advection, the spatial arrangement of bacteria and the colony extension from an adsorbing boundary [17]. Furthermore, it has been suggested that AIs could work also as transducers of host cues [18].…”
Section: Introductionmentioning
confidence: 99%